Serum Serotonin Levels among Homosexual and Heterosexual Men - Santoso Santoso; Lusiana Batubara (MEDIA MEDIKA INDONESIANA, 2013)
ABSTRACT Background: Variations in sexual preferences and orientations have both proximate and ultimate causes. Serotonin (5-HT) system is a key in the regulation of reward-related behaviors, from eating, drinking to sexual activity. Recent study demonstrated that a serotonin level is involved in sexual preference in rodent as animal models. This study focuses on the profile of serotonin levels from blood among homosexual compared to heterosexual men.Methods: Eight adult (34.5±7.69) homosexual men were purposively collected from homosexual communities in Surabaya, as well thirteen adult (27.61±5.14) heterosexual men from Semarang. Complete psychological examinations were done, then serum serotonin levels were measured using ELISA. Furthermore age and Zung-self-rating depression scale were cross matched, then serum serotonin levels were tested using Mann-Whitney U Test to determine the difference of serotonin levels among two groups.Results: Our data demonstrated that 25% of homosexual men suffered from depression. There was no difference on serum serotonin levels among homosexual men compared to heterosexual men (p=0.41).Conclusion: There is no significant difference on serum serotonin levels among homosexual and to heterosexual men.Keywords: Sexual preferences, homosexual, heterosexual, serotonin, depressionABSTRAKKadar serum serotonin pada laki-laki homoseksual dan heteroseksualLatar belakang: Variasi dalam preferensi dan orientasi seksual memiliki beberapa faktor penyebab. Serotonin (5-HT) merupakan kunci dalam pengaturan perilaku mulai dari makan, minum sampai aktivitas seksual. Penelitian terdahulu menyebutkan bahwa kadar serotonin memiliki peran dalam penentuan preferensi seksual pada tikus. Penelitian ini bertujuan untuk menganalisis kadar serotonin darah pada laki-laki homoseksual dan heteroseksual.Metode: Delapan laki-laki homoseksual dewasa secara purposif (34,5±7,69 tahun) diambil dari komunitas homoseksual di Surabaya dan 13 laki-laki heteroseksual dari Semarang (27,61±5,14 tahun), kemudian dilakukan skrining tanda depresi dengan menggunakan Zung-self-rating depression scale. Kadar serotonin serum diperiksa dengan menggunakan metode ELISA. Data yang diperoleh kemudian dianalisis dengan menggunakan uji Mann-Whitney U untuk melihat perbedaan kadar serotonin serum pada kedua kelompok.Hasil: 25% laki-laki homoseksual mengalami depresi, dan tidak ada perbedaan kadar serotonin pada serum laki-laki homoseksual maupun heteroseksual (p=0.41).Simpulan: Tidak terdapat perbedaan antara kadar serotonin serum laki-laki homoseksual dengan heteroseksual.